Impact of hospital volume on hospital mortality, length of stay and total costs after pancreaticoduodenectomy. (24th February 2014) - Yoshioka, R; Yasunaga, H; Hasegawa, K; Horiguchi, H; Fushimi, K; Aoki, T; Sakamoto, Y; Sugawara, Y; Kokudo, N
Abstract: Background: High morbidity and mortality rates after pancreaticoduodenectomy (PD) have led to concentration of this surgery in high-volume centres, with improved outcomes. The extent to which better outcomes might be apparent in a healthcare system where the mortality rate is already low is unclear. Methods: The Japanese Diagnosis Procedure Combination database was used to identify patients undergoing PD between 2007 and 2010. Patient data included age, sex, co-morbidities at admission, type of hospital, type of PD, and the year in which the patient was treated. Hospital volume was defined as the number of PDs performed annually at each hospital, and categorized into quintiles: very low-, low-, medium-, high- and very high-volume groups. The Charlson co-morbidity index was calculated using the International Classification of Diseases, tenth revision, codes of co-morbidities. Results: A total of 10 652 patients who underwent PD in 848 hospitals were identified. The overall in-hospital mortality rate after PD was 3·3 per cent (350 of 10 652), and for the groups ranged from 5·0 per cent for the very low-volume group to 1·4 per cent for the very high-volume group ( P < 0·001). Multivariable analysis revealed a significant linear relationship between higher hospital volume and shorter postoperative length of stay compared with the very low-volume group, and between increasing hospital volume and lower total costs. Conclusion: A significant relationship exists between increasing hospital volume, lower in-hospital mortality, shorter length of stay and lower costs for patients undergoing PD in Japan. Centralization of PD in this healthcare system is therefore justified. Abstract : The volume effect is important even when mortality is low